EXTRACTION AND CHARACTERIZATION: STARCH, PROTEIN, AND OIL OF DURIAN SEEDS (DURIO ZHYBETHINUS MURR.) FROM WEST SUMATRA (Nativa, 2026)
Durian is a seasonal fruit widely consumed in Indonesia, with its seeds often left unutilized. This study explores the physicochemical characteristics of flour, starch, protein, and oil extracted from durian seeds sourced from West Sumatra. Conducted in two stages—extraction and characterization—the study applied a descriptive quantitative method. Durian seed starch yielded 9.42% with round and irregular granules, 18.17% amylose, 81.83% amylopectin, water absorption of 2.11 ml/g, oil absorption of 2.91 ml/g, and exhibited a type C gelatinization profile with a peak viscosity of 3059.5±1496.55 cP. Thermal properties showed an initial gelatinization temperature of 65.17°C and degradation at 297.55°C. The starch had a °Hue value of 267.40 and whiteness of 89.85%. Protein concentrate yielded 0.16% with 72.30% protein, containing six amino acids suitable for food applications like crackers, noodles, and complementary foods. Oil yield was 0.25%, containing unsaturated fatty acids such as linoleic (19.77%), stearic (11.78%), and conjugated linoleic acid (11.27%), alongside saturated fatty acids like hexadecanoic acid (30.38%). Durian seed flour yielded 28.60%, with moisture (9.33%), ash (2.67%), protein (4.91%), °Hue (101.03), whiteness (87.59%), and sulfite residue (58.05 ppm), complying with Indonesian health standards. These findings suggest durian seeds' high potential for food industry applications.